Developmental genetics of a temperature-sensitive RNA polymerase II mutation in Drosophila melanogaster. - Mortin, M.A.; Kaufman, T.C. (Molecular and General Genetics, 1982)
Purified RNA polymerase II (RNA nucleotidyl-transferase; EC 2.7.7.6) extracted from flies possessing lesions in the Ultrabithorax-like (Ubl) locus of Drosophila melanogaster has altered activity in vitro (Greenleaf et al. 1979, 1980; Coulter and Greenleaf 1982). This strongly suggests that the Ubl locus encodes a subunit of RNA polymerase II. Ethyl methanesulfonate was used to induce a temperature-sensitive mutation in this locus. Flies either homozygous or hemizygous for this new X-linked mutation (Ublts) display viability comparable to that of wild-type flies at 22 degrees C but are lethal at 29 degrees C. The temperature-sensitive period for Ublts flies is between gastrulation (6 h, 29 degrees C) and pupation (9-10 days, 22 degrees C). Zygotes shifted from 22 degrees C to 29 degrees C die at either the late embryonic or first larval instar stage while temperature shifts of second and third instar larvae result in the lethal phase occurring at the pupal stage. Most pupae shifted from 22 degrees C to 29 degrees C undergo metamorphosis and eclose as adults. Adults are viable if placed at 29 degrees C; however, all females and some males become sterile if maintained at this temperature. Somatic recombination was used to induce clones homozygous for a null allele of Ubl at different stages of development. Clones of this null allele appear to be cell lethal indicating that the Ubl+ gene product is required at all stages of development. The viability of Ublts pupae and adults at 29 degrees C may result from only a partial reduction in activity caused by the mutation at this nonpermissive temperature.